2020
DOI: 10.3329/bjb.v49i3.49327
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-anatomical investigations of three critically endangered endemic species

Abstract: Morphological and anatomical characteristics of Crocus ancyrensis Herb. (Maw) (endemic), C. antalyensis Mathew (endemic), C. chyrsanthus (Herb.) Herb. and C. sativus L. which are distributed in Central Anatolia, Turkey have been studied. The morphological characteristics of species have been compared with the Flora of Turkey. In anatomical studies, transverse sections of root, stem and leaf have been examined and supported by illustration. In addition, the determination of the anatomical characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Sayarer et al (2015) analyzed Crocus ancyrensis and found that safranal, α-isophorone and β-isophorone are the main components (Sayarer, 2015). In another study, Küçük et al (2019) revealed that chemical composition of Crocus ancyrensis from Eskişehir region, Türkiye is compatible with the findings in Sayarer's study and contained β-Isophorone (14.4%), heptanal (11.5%) and heneicosane (8.5%) (Küçük et al, 2019). For this reason, they have reported that Crocus ancyrensis could be an alternative source to Crocus sativus L., which contains safranal (77.9%), α-isophorone (13.5%), and β-isophorone (2.2%).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Sayarer et al (2015) analyzed Crocus ancyrensis and found that safranal, α-isophorone and β-isophorone are the main components (Sayarer, 2015). In another study, Küçük et al (2019) revealed that chemical composition of Crocus ancyrensis from Eskişehir region, Türkiye is compatible with the findings in Sayarer's study and contained β-Isophorone (14.4%), heptanal (11.5%) and heneicosane (8.5%) (Küçük et al, 2019). For this reason, they have reported that Crocus ancyrensis could be an alternative source to Crocus sativus L., which contains safranal (77.9%), α-isophorone (13.5%), and β-isophorone (2.2%).…”
Section: Introductionmentioning
confidence: 90%
“…Besides, it's found that alcohol and water extracts of Crocus ancyrensis showed an inhibitory effect on Aeromonas hydrophila bacterial fish pathogens (Turker et al, 2009). On the other hand, Küçük et al (2019) reported that local people used Crocus ancyrensis tea as a traditional medicine for abdominal pain and diuretic (Küçük et al, 2019). However, there are limited number of studies on the Crocus ancyrensis extracts in the literature (Gunbatan et al, 2016;Küçük et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological and anatomical characteristics of four species: C. sativus, C. ancyrensis., C. antalyensis, C. chyrsanthus were studied by Kyuchuk S. and Soarer M. The key morphological differences between the species are the color of the perianth segments and the shape of the cross section of the leaf blade [13]. Akyul Y. and his colleagues [14] presents the morphological and anatomical signs of C. asumaniae and C. mathewii, where the characteristic feature is the presence of sclerenchymal tissues around the leaf vascular bundles.…”
mentioning
confidence: 99%